Distribución inusual y potencial de la garrapata común del ganado, Rhipicephalus (Boophilus) microplus, en zonas tropicales de alta montaña de los Andes colombianos (2015)
Potential areas of distribution of the common cattle tick Rhipicephalus (Boophilus) microplus in the Altiplano Cundiboyacense are presented, using two algorithms of ecological niche modeling (Maxent and Classification Trees). The algorithms were complementary, with excellent and significant returns, registering AUC (0.70 and 0.90 Maxent Classification Trees), and low values of omission errors (0.00% and 4.6% Maxent Classification Trees). The landscape along with the presence of the host, altitude, precipitation, temperature and humidity of the first wet quarter, were the most important variables in modeling. The north-eastern region of the Altiplano has the best potential for the establishment of this species.